Innovative Practice and Exploration of Knowledge – Graph - Supported Teaching Reform in Linear Algebra - Shi, Qinxian (Journal of Educational Research and Policies, 2025)
With the rapid development of information technology, knowledge graphs have become an important tool for representing structured knowledge and have introduced new possibilities for educational reform. Drawing on practical teaching experience, this study systematically examines a model that integrates knowledge graphs into the instruction of linear algebra. It discusses the construction of the knowledge graph, related pedagogical application strategies, and the resulting implementation outcomes. Findings indicate that knowledge graphs can effectively integrate instructional resources, optimize curriculum design, and significantly enhance students’ autonomous learning and practical application abilities. The model provides a valuable reference for reforming foundational courses in science and engineering within the context of smart education.